The Influence Of Accountability And Transparency On The Management Of Health Operational Assistance Funds (BOK) - Muhammad Naim; Nursyidah; Lidia Nurliana; Sarah Nabila; Fahra Vinola Isma Dwiyani (Journal Informatic, Education and Management (JIEM), 2025)
This study aims to determine the effect of accountability and transparency on the management of the Health Operational Assistance (BOK) fund at Puskesmas Jeumpa, Bireuen Regency. The topic was chosen due to the crucial role of BOK in supporting promotive and preventive health programs, and the frequent issues of fund mismanagement. The research employed a quantitative approach using a survey method. Primary data were collected through questionnaires with a Likert scale of 1–5 distributed to 73 respondents and analyzed using multiple linear regression. The findings indicate that both accountability and transparency have a positive and significant effect, both partially and simultaneously, on BOK fund management. The coefficient of determination of 78.8% shows that these two variables explain most of the variation in fund management. In conclusion, higher levels of accountability and transparency lead to better BOK fund management. It is recommended that the health center and local government strengthen accountability mechanisms, improve information disclosure, and enhance supervision to optimize the effective and efficient use of BOK funds.